2006
DOI: 10.1002/nau.20253
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of bladder storage function by α1‐blocker depends on the suppression of C‐fiber afferent activity in rats

Abstract: These results suggest that naftopidil has an inhibitory effect on C-fiber afferents in the lumbosacral spinal cord, improving BC during the storage phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…15 In Japan, like tamsulosin, naftopidil is prescribed widely for patients with LUTS associated with BPH. 16 Several reports demonstrated that naftopidil improved bladder capacity and relaxed voiding via inhibition of afferent nerve activity, 17,18 and clinically improved not only obstructive voiding symptoms but also storage symptoms associated with BPH. 19,20 Kyprianou and Benning demonstrated that doxazosin and terazosin (quinazoline-derived a-1 adrenoceptor antagonists) had growth-inhibitory effects in human prostate cancer cell lines.…”
mentioning
confidence: 99%
“…15 In Japan, like tamsulosin, naftopidil is prescribed widely for patients with LUTS associated with BPH. 16 Several reports demonstrated that naftopidil improved bladder capacity and relaxed voiding via inhibition of afferent nerve activity, 17,18 and clinically improved not only obstructive voiding symptoms but also storage symptoms associated with BPH. 19,20 Kyprianou and Benning demonstrated that doxazosin and terazosin (quinazoline-derived a-1 adrenoceptor antagonists) had growth-inhibitory effects in human prostate cancer cell lines.…”
mentioning
confidence: 99%
“…Several animal studies using rats and mice have demonstrated that the micturition reflex is facilitated by the α1D-AR subtype on urothelial cells 18,19. In addition, it has been demonstrated that naftopidil has an inhibitory effect on C-fiber afferents because the drug increases bladder capacity in rats with cerebral infarction, but not in C-fiber desensitized rats with cerebral infarction 20. Thus, naftopidil, with a higher affinity for the α1D-AR subtype, may contribute to improving detrusor overactivity through the blockade of the α1D-AR subtype not only in the prostate but also in nonprostatic organs.…”
Section: Rationale For Naftopidil Treatment Of Luts Suggestive Of Bphmentioning
confidence: 99%
“…Previous studies included factors within their methodologies that may limit the clinical relevance of their results. For example, many animal studies of afferent nerve activity from the LUTS have investigated the effect of a single‐dose of α 1 ‐AR antagonists 13,14 rather than the chronic administration of these agents, which would more closely approximate clinical conditions. Moreover, experiments without anesthesia are preferable to those with anesthesia, which could otherwise affect urinary function 15 .…”
Section: Introductionmentioning
confidence: 99%